(untitled) (Proceedings of Southern Federal University. Philology, 2022)
DOI 10.18522/1995-0640-2022-3-43-52 The article is devoted to the study of comforting communicative strategy. The tactics and linguistic means realizing it differ from one lingua-culture to another. The relevance of the article is due to the need for further study of this strategy in German lingua-culture. The purpose of this work is to define the tactics and linguistic means that realize comforting strategy in German speech, as well as their national peculiarities. According to the analysis of empiric material, the following tactics can be distinguished: soothing tactics, distraction tactics, empathy tactics, optimism tactic, fatalism tactic, support tactics, generalization tactics, mobilization tactics, tactics of perspective change, of feelings explication, of reference to personal experience, of opponent’s criticism, of ways of coping suggestion. The author comes to the conclusion that the realization of comforting strategy in German speech reflects the following national peculiarities. The speakers appeal to the listener’s logic and give a detailed argumentation of their ideas. They criticize the lack of rationality in the other’s behavior. The idea of a norm is of great importance. The norm refers to the emotional stability, peace of mind and confidence. A comforting message aims to help the consoled get back to this norm. It is also connected with Ordnung, Sicherheit concepts A comforter can also appeal to the Pflicht concept. The study also shows that the speaker tries to alleviate the listener’s feeling of uncertainty and appeals to Zeit concept. Key words: comforting strategy, German lingua-culture, cooperation, traumatic situation, national peculiarities.